Post‐operative mortality and recurrence patterns in pancreatic cancer according to KRAS mutation and CDKN2A, p53, and SMAD4 expression - Yohei Masugi; Manabu Takamatsu; Mariko Tanaka; Kensuke Hara; Yosuke Inoue; Tsuyoshi Hamada; Tatsunori Suzuki; Junichi Arita; Yuki Hirose; Yoshikuni Kawaguchi; Yousuke Nakai; Atsushi Oba; et al. (Wiley, 2023)
Abstract Alterations in KRAS, CDKN2A (p16), TP53, and SMAD4 genes have been major drivers of pancreatic carcinogenesis. The clinical course of patients with pancreatic cancer in relation to these driver alterations has not been fully characterised in large populations. We hypothesised that pancreatic carcinomas with different combinations of KRAS mutation and aberrant expression of CDKN2A, p53, and SMAD4 might show distinctive recurrence patterns and post‐operative survival outcomes. To test this hypothesis, we utilised a multi‐institutional cohort of 1,146 resected pancreatic carcinomas and assessed KRAS mutations by droplet digital polymerase chain reaction and CDKN2A, p53, and SMAD4 expression by immunohistochemistry. Multivariable hazard ratios (HRs) and 95% confidence intervals (CIs) for disease‐free survival (DFS) and overall survival (OS) were computed according to each molecular alteration and the number of altered genes using the Cox regression models. Multivariable competing risks regression analyses were conducted to assess the associations of the number of altered genes with specific patterns of recurrence. Loss of SMAD4 expression was associated with short DFS (multivariable HR, 1.24; 95% CI, 1.09-1.43) and OS times (multivariable HR, 1.27; 95% CI, 1.10-1.46). Compared to cases with 0-2 altered genes, cases with three and four altered genes had multivariable HRs for OS of 1.28 (95% CI, 1.09-1.51) and 1.47 (95% CI, 1.22-1.78), respectively (ptrend < 0.001). Patients with an increasing number of altered genes were more likely to have short DFS time (ptrend = 0.003) and to develop liver metastasis (ptrend = 0.006) rather than recurrence at local or other distant sites. In conclusion, loss of SMAD4 expression and an increasing number of altered genes were associated with unfavourable outcomes in pancreatic cancer patients. This study suggests that the accumulation of the four major driver alterations can confer a high metastatic potential to the liver, thereby impairing post‐operative survival among patients with pancreatic cancer.